Pengaruh Jumlah Kunjungan Wisatawan, Jumlah Objek Wisata dan Penerimaan Retribusi Objek Wisata Terhadap Pendapatan Asli Daerah Kabupaten Bone Bolango Gorontalo Tahun 2018-2022 - Mohamad Rizki Sadaga; Zain Olilingo; Ayu Rakhma Wuryandini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to determine the extent to which the number of tourist visits (X1), the number of tourist attractions (X2) and the receipt of tourist attraction levies (X3) have on local original income (Y) in Bone Bolango Regency, Gorontalo from 2018 to 2022. The data collection technique in this research was obtained by researchers using the documentation method by studying books and journals published by the government by collecting data on reports on the number of tourists, number of tourist attractions, tourist attraction levies and local original income in Bone Bolango Regency from 2018 to 2022. 2022. The type of data used in this research is secondary data. This research analysis technique uses multiple linear regression analysis techniques. This type of research uses quantitative research. Hypothesis testing in this research uses the multiple linear regression analysis method with the SPSS version 25 program. The results obtained by researchers show that the number of tourist visits, number of tourist attractions and receipt of tourist attraction levies have a significant influence on the Regional Original Income of Bone Regency Bolango, Gorontalo. This illustrates that the higher the number of tourist visits to tourist destinations in Bone Bolango Regency, the higher the PAD for the tourism sector in Bone Bolango Regency, the more tourist attractions are well managed, the greater the contribution of the tourism sector to the regional economy and this shows that the increase in levies from entrance tickets, parking fees, and sales of local products and services around tourist attractions is well managed. From the results of the coefficient of determination test (Adjusted R Square), it was 19.2%, with the remaining 80.8% being explained by factors not tested in this study.